THE EVALUATION OF THE GENERAL HEALTH CONDITION AND THE DEVELOPMENT OF PREVENTIVE MEASURES IN WOMEN AFFECTED BY MASTOPATHY (American Journal of Interdisciplinary Research and Development, 2024)
Women seeking medical attention at the Tashkent City Oncology Dispensary due to mastopathy account for 55-60% of the total number of patients from the Chilonzor, Uchtepa, and Shaykhontokhur districts. This situation does not indicate that the disease is more common in certain districts, but rather may reflect a higher level of medical awareness among the population. When studying the seasonality of mastopathy, it was found that most cases occur in the spring and autumn.